Queer Words, Queer Images : Communication and the Construction of Homosexuality - Ringer, R. Jeffrey; Ringer, R. Jeffrey (Book collections on Project MUSE., 1994)
The logic of folly in the political campaigns of Harvey Milk / Karen A. Foss -- On the owning of words: reflections of San Francisco arts and athletics vs. United States Olympic committee / Paul Siegel -- Die non: gay liberation and the rhetoric of pure tolerance / James Darsey -- Reflections on gay and lesbian rhetoric / James W. Chesebro -- Guilt by association: homosexuality and AIDS on prime-time television / Emile C. Netzhammer and Scott A. Shamp -- Whose desire? Lesbian (non)sexuality and television's perpetuation of hetero/sexism / Darlene M. Hantzis and Valerie Lehr -- Old strategies for new texts : how American television is creating and treating lesbian characters / Marguerite J. Moritz -- What is wrong with this picture? Lesbian women and gay men on television / Larry Gross -- A portrait of the adolescent as a young gay: the politics of male homosexuality in young adult fiction / Kirk Fuoss -- Self as other: the politics of identity in the works of Edmund White / Nicholas F. Radel -- Female athlete = lesbian : a myth constructed from gendex [sic] role expectations and lesbiphobia / Karen Peper -- The politics of self and other / Lynn C. Miller -- Self-disclosure behaviors of the stigmatized: strategies and outcomes for the revelation of sexual orientation / Timothy Edgar -- Gender and relationship crises : contrasting reasons, responses, and relational orientations / Julia T. Wood -- Gay and lesbian couple relationships / Mary Anne Fitzpatrick [and others] -- Reflections on interpersonal communication in gay and lesbian relationships / Dorothy S. Painter -- Performing the (lesbian) self : teacher as text / Jacqueline Taylor -- Coming out to students: notes from the college classroom / Elenie Opffer -- Coming out in the classroom: faculty disclosures of sexuality / R. Jeffrey Ringer -- Ways of coming out in the classroom / Mercilee M. Jenkins.